China’s Quiet Diplomacy: Assessing its Role in Saudi-Iran Reconciliation Process - Ali, Najaf; Mehdi, Asif; Ali, Kousar (Annals of Human and Social Sciences, 2024)
This study conducts a thorough analysis of China’s efforts to bring Saudi Arabia and Iran closer together. The objective of the study is to understand the factors that lead China to play its role in reconciliation process. The research utilizes a qualitative methodology by examining official statements, policy papers, research papers, and media narratives to explain China’s diplomacy and policies about the relations between Saudi Arabia and Iran. This study seeks to clarify the factors that have influenced China’s participation in the efforts to bring Tehran and Riyadh together, as well as the obstacles faced by it in contributing significantly to these efforts. The results show that in order to protect their respective national interests, Tehran and Riyadh were willing to restart bilateral relations prior to Beijing efforts, and China played minor role in the process of reconciliation. China has consistently taken a cautious approach to the Saudi-Iranian relations, owing its geopolitical and economic interests. China’s calculated influence in Middle Eastern diplomacy is a result of the complex dynamics of the area and the dominance of other powerful countries. This analysis contributes to a broader understanding of Saudi-Iran relations, China’s foreign policy objectives in the Middle East, and its role in regional dynamics. It also highlights the challenges and limitations faced by China in its efforts to mediate between Saudi Arabia and Iran.